Acute Trigeminal Neuralgia Associated with Initiation of Emtricitabine/Tenofovir for HIV Pre-Exposure Prophylaxis. (13th March 2018) - Van Slyke, Loraine; Scott, Mia
HIV pre-exposure prophylaxis (PrEP) with emtricitabine (FTC) and tenofovir disoproxil fumarate (TDF) fixed-dose combination (FTC/TDF) is undergoing rapid scale-up in the United States. While FTC/TDF is typically well tolerated, to our knowledge, cranial nerve pathology associated with FTC/TDF has not been previously described. We report the case of a 35-year-old patient who began FTC/TDF PrEP and developed acute trigeminal neuralgia. The neurologic symptoms resolved after treatment discontinuation and recurred upon rechallenge, resulting in permanent discontinuation of PrEP treatment.